Lynx1 Shifts α4β2 Nicotinic Receptor Subunit Stoichiometry by Affecting Assembly in the Endoplasmic Reticulum - Nichols, Weston A. (J Biol Chem, 2014)
Glycosylphosphatidylinositol-anchored neurotoxin-like receptor binding proteins, such as lynx modulators, are topologically positioned to exert pharmacological effects by binding to the extracellular portion of nAChRs. These actions are generally thought to proceed when both lynx and the nAChRs are on the plasma membrane. Here, we demonstrate that lynx1 also exerts effects on α4β2 nAChRs within the endoplasmic reticulum. Lynx1 affects assembly of nascent α4 and β2 subunits and alters the stoichiometry of the receptor population that reaches the plasma membrane. Additionally, these data suggest that lynx1 shifts nAChR stoichiometry to low sensitivity (α4)(3)(β2)(2) pentamers primarily through this interaction in the endoplasmic reticulum, rather than solely via direct modulation of activity on the plasma membrane. To our knowledge, these data represent the first test of the hypothesis that a lynx family member, or indeed any glycosylphosphatidylinositol-anchored protein, could act within the cell to alter assembly of a multisubunit protein.